2007
DOI: 10.1038/sj.onc.1210268
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced G2/M checkpoint response requires ERK1/2 activation

Abstract: Following DNA damage, cells undergo G2/M cell cycle arrest, allowing time for DNA repair. G2/M checkpoint activation involves activation of Wee1 and Chk1 kinases and inhibition of Cdc25A and Cdc25C phosphatases, which results in inhibition of Cdc2 kinase. Results presented in this report indicate that c-irradiation (IR) exposure of MCF-7 cells resulted in extracellular signal regulated protein kinase 1 and 2 (ERK1/2) activation and induction of G2/M arrest. Furthermore, inhibition of ERK1/2 signaling resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 32 publications
7
119
0
2
Order By: Relevance
“…Requirement for ERK1 and ERK2 activation has been demonstrated for DNA damage-induced G 2 /M arrest in mammalian cells (Chou et al, 2007;Yan et al, 2007). In this study, we demonstrated that the lack of activation and persistence of phosphorylated ERK1 and ERK2 proteins after alkylation damage correlate with lack of G 2 /M arrest in H2AX-deficient cells.…”
Section: Discussionsupporting
confidence: 58%
“…Requirement for ERK1 and ERK2 activation has been demonstrated for DNA damage-induced G 2 /M arrest in mammalian cells (Chou et al, 2007;Yan et al, 2007). In this study, we demonstrated that the lack of activation and persistence of phosphorylated ERK1 and ERK2 proteins after alkylation damage correlate with lack of G 2 /M arrest in H2AX-deficient cells.…”
Section: Discussionsupporting
confidence: 58%
“…decreasing Chk1 activation and repression of G 2 -M arrest (23). Taken together, these facts suggest that ERK activation may play a key role in the regulation of the ATR/Chk1-dependent G 2 -M checkpoint in cells with damaged DNA.…”
Section: Introductionmentioning
confidence: 60%
“…Celecoxib can also induce cell cycle arrest, apoptosis, or ERK activation through a COX-2-independent mode (21,22). These facts indicate that celecoxib acts through COX-2-dependent and COX-2-independent pathways (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…We next determined if co-treatment of HeLa cells with Cr(VI) and caffeine would have an effect on modulating cell cycle distributions, because caffeine is capable of weakening the DNA damage checkpoint by inhibiting activities of ATM/ATR. 15,16 Caffeine treatment alone did not have any noticeable effects on perturbing cell cycle distribution, whereas Cr(VI) greatly enriched S-phase cells (Figs. 3A and 4A).…”
Section: Resultsmentioning
confidence: 99%